Enhanced Direct Converter with Minimum Switching Devices and Variable Capacitor - Konarik, Roman; Prazenica, Michal; Kascak, Slavomir (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with a single-leg direct (matrix) converter with minimum switching devices and enhancements for improving current THD and phase advancing with the use of variable (switched) capacitors. This converter supplies single-phase induction motor (SPIM). Due to strongly non-harmonic phase voltages, an additional circuit should be used, so that phase-currents can be nearly harmonic. Simulations are done under both resistive-inductive load and motoric load. Speed control was realized using vector control with current controlled pulse-width-modulation (hysteresis regulator). Verification of such a drive system was done using dSpace environment. Preliminary results are given in the paper.